The provocation of the senses in contemporary theatre - Di Benedetto, Stephen (New York : Routledge, 2010)
Our sensing bodies: a multidisciplinary approach to understanding live theatrical experience -- Scintillating visions and visual perception: how light, movement, and stage space capture our attention and stimulate our brains -- Attendant to touch: cutaneous stimulation and its expressive capabilities -- Noses, tongues, and other surprising possibilities: harnessing olfaction and gustation in performance -- Aural landscapes: voices, noises, vibrations, and other quivering stimulators of cochlear perception -- The sentient body: guiding somatic responses within performative structures.
boek